Redefining high-k dielectric materials vision at nanoscale for energy storage: A new electrochemically active protection barrier. (1st September 2021) - Valero, Anthony; Mery, Adrien; Gaboriau, Dorian; Dietrich, Marc; Fox, Maggie; Chretien, Jeremy; Pauc, Nicolas; Jouan, Pierre Yves; Gentile, Pascal; Sadki, Saïd
Abstract: Dielectric materials have been used for decades for energy applications where their insulation and polarizability properties are critical. In the energy storage field, most material scientists envision high-k dielectric layers in contact with an active material only as an insulating passivation layer. In microelectronics, this concept has been modified with the study of dielectrics at nanoscale level revealing interesting properties scarcely known by other fields. We propose to reconsider the vision of high-k dielectric materials for energy at nanoscale specifically. Based on microelectronic measurement techniques and nanometric control of dielectric thickness by Atomic Layer Deposition (ALD), an ultra-thin pinhole-free alumina (Al2 O3 ) layer on a silicon nanowire (SiNW) is shown to display thickness dependent tunneling electrical conduction. This result brings a new light on this material class in the energy field and allows original approaches toward achieving scientific leaps. As an illustrative application, a silicon based micro-supercapacitor (MSC) protected by 3 nm of alumina dielectric layer exhibits Electrical Double Layer Capacitance (EDLC) by means of tunneling current in aqueous electrolyte, an unprecedented result for this material, with outstanding lifetime capacity retaining 99% of its initial capacitance after 2 million cycles. Extended to multiple energy materials, such method could lead to notable progress. Graphical abstract: Image, graphical abstract